Water and Sediment Process Variation in Jingjiang River in the Middle Reaches of the Yangtze River and Response Analysis of Flow Capacity of Three Outlets - SHEN Jian; YUAN Song (Renmin Zhujiang)
The Jingjiang reach of the middle reaches of the Yangtze River is connected to Dongting Lake through three outlets,forming an extremely complex and far-reaching relationship between the rivers and lakes.The operation of the Three Gorges Project has changed the natural water and sediment process in the Jingjiang River downstream of the dam.This leads to “flattening” flood processes in the main stream,extended middle water period,and an increase in low flow,which has promoted the continuous response of the three outlets to the above water and sediment conditions.Meanwhile,this paper employs a series of long-term measured hydrological consolidation data and river channel terrain observation results from nearly 70 years.Based on this,the response characteristics of the three outlets to the water and sediment variation process of the Jingjiang River are analyzed,and the flow and sediment diversion,river regime,and erosion and sedimentation evolution laws in the entrance area are summarized.The results show that in the same inflow conditions before and after the operation of the Three Gorges Project,the diversion ratio of three outlets decreases,and the sediment diversion corresponds to the sediment from the upstream branch city.Additionally,the sediment diversion ratio continues its gradually increasing trend.After the impoundment and operation of the Three Gorges Reservoir,the riverbed of three outlets is generally in a state of erosion,with a total erosion amount of 51.47 million m3 from 2003 to 2011 and 99 million m3 from 2011 to 2016.The entrance areas have been expanded,but the actual flow capacity has not been significantly improved.